Violations of the Use of Sarmat Missiles as a Chemical Weapon in Armed Conflicts in International Humanitarian Law - Butar–Butar, Alan Mahendi; Nasir Sitompul, Muhammad (Universitas Ekasakti, 2023)
The purpose of this work is to find out what are the regulations for the use of Sarmat missiles according to international treaties (1), what are the violations of the use of Sarmat missiles according to the Chemical Weapons Convention of 1997 (2), what is the form of responsibility for the use of Sarmat missiles according to the Weapons Convention of 1997. (3) what is the form of responsibility for the use of Sarmat missiles according to the 1997 Weapons Convention using normative legal research methods. concluded.: the efforts of countries to achieve world peace and mutual security of each country through the regulation and prohibition of chemical weapons are consistently implemented by countries, namely by establishing protocols prohibiting the use of gases that cause asphyxiation, poisonous gases / other gases in war and warfare. This method of using bacteria became known as the Geneva Protocol of 1925, the Chemical Weapons Convention of 1992, the Additional Protocol of 1977, and the Hague Convention of 1907. The existence of martial law has become a legal norm that the international community must abide by in wars and armed conflicts arising from sovereignty issues. The regulation of war and armed conflict in each UN member state is now a measure of the extent to which compliance with international humanitarian law treaties can be fairly enforced through the International Criminal Court.